Locating the Mediterranean Connections and Separations across Space and Time - Rommel, Carl; Viscomi, Joseph (Helsinki University Press, 2022)
"Until today, anthropological studies of locality have taken primary interest in local subjects leading local lives in local communities. Through a shift of conceptual emphasis from locality to location, the present volume departs from previous preoccupations with identity and belonging. Instead, Locating the Mediterranean brings together ethnographic examinations of processes that make locations and render them meaningful. In doing so, it stimulates debates on the interplay between location and region-making in history as well as anthropology. The volume's deeply empirical contributions illustrate how historical, material, legal, religious, economic, political, and social connections and separations shape the experience of being located in the geographical space commonly known as the Mediterranean region. Drawing from research in Melilla, Lampedusa, Istanbul, Nefpaktos/Lepanto, Tunisia, Beirut, Marseille, and elsewhere, the volume articulates location through the overlapping and incorporation of multiple social and historical processes. Individual contributions are linked by the pursuit to rethink the conceptual frames deployed to study the Mediterranean region. Together, the volume's chapters challenge strict geopolitical renderings of Europe, the Middle East, and North Africa and suggest how the 'Mediterranean' can function as a meaningful anthropological and historical category if the notion of 'location' is reinvigorated and conceptualised anew."